2021
DOI: 10.1101/2021.09.05.458990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pilot identification of the Live-1/Prox-1 expressing lymphatic vessels and lymphatic elements in the unaffected and affected human brain

Abstract: We report here a pilot identification of the presence of the lumenized Lyve-1/Prox-1-expressing vessels with distinct walls composed of a single endothelial layer in the unaffected brain and with intraventricular hemorrhages. These lymphatic vessels (LVs) have valves and an undulating shape in the distal region that is the classical characteristic of lymphatic precollectors. Furthermore, we identified Lyve-1/Prox-1-expressing lymphatic elements in the enlarged perivascular spaces. These pioneering results migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Meanwhile, with the deeper understanding of brain-related lymphatic networks, a number of studies were committed to delivering drugs to the brains by deep cervical lymph nodes (dCLNs) bypassing the blood–brain barrier (BBB), which also inspired our interests. As a result, we designed a long-acting injectable lyotropic liquid crystalline implant encapsulating both cilostazol and donepezil hydrochloride (an FDA-approved symptomatic relief agent for AD), which was delivered by dCLNs. By injecting a drug-loaded platform into dCLNs, we found that brain-entering efficiency of both drugs was elevated when compared with oral and subcutaneous delivery, confirming the therapeutic advantage of this delivery route.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, with the deeper understanding of brain-related lymphatic networks, a number of studies were committed to delivering drugs to the brains by deep cervical lymph nodes (dCLNs) bypassing the blood–brain barrier (BBB), which also inspired our interests. As a result, we designed a long-acting injectable lyotropic liquid crystalline implant encapsulating both cilostazol and donepezil hydrochloride (an FDA-approved symptomatic relief agent for AD), which was delivered by dCLNs. By injecting a drug-loaded platform into dCLNs, we found that brain-entering efficiency of both drugs was elevated when compared with oral and subcutaneous delivery, confirming the therapeutic advantage of this delivery route.…”
Section: Resultsmentioning
confidence: 99%
“…Because MLVs play an important role in draining brain tissues and removing toxins and metabolites from the brain, future treatments for reversible forms of dementia are expected to involve stimulation of lymphatic drainage processes. Given the growing evidence of the existence of lymphatic vessels directly in the human brain [ 292 , 293 , 294 , 295 ], and not only in its meninges [ 296 , 297 ], technologies for activating lymphatic drainage processes will contribute to progress in the treatment of a wide number of brain diseases associated with dysfunction of the cerebral lymphatic system, such as AD, Parkinson’s disease, brain trauma and oncology [ 44 , 45 , 46 , 47 , 48 , 49 , 118 , 119 , 162 , 275 , 276 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, over two centuries, scientific evidence has accumulated providing the presence of drainage processes in the CNS [ 1 , 3 ]. It is still unknown whether LVs exist directly in the CNS [ 4 , 5 ]. However, the presence of LV in the brain’s meninges is widely accepted [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%